معوقات العملية الاتصالية عند المنتخبين المحليين وتأثيرها على التنمية المحلية في المجتمع الجزائري The Obstacles Of Communication Process And Its Influence On The Development In Algerian Society - كريمة, فلاحي; السعيد, رشيدي (Université de M'sila, 2020)
ملخص : تعتبر المجالس الشعبية البلدية الخلايا القاعدية لأي نظام سياسي وهي اللبنة الأولى في الهيكل الهرمي للمؤسسات الإدارية كما تعد الخلية الأساسية التي عن طريقها تتحقق التنمية المحلية. ولكن غالبا ما نجد مجموعة من المعوقات تقف حجر عثرة أمام تحقيق هذه الأخيرة، حيث يمكننا أن نعتبر غياب القنوات الاتصالية بين أفرادها أحد أهم هذه المعوقات، الشيء الذي جعلنا نطرح التساؤلات التالية: 1/ ما هي معوقات العملية الاتصالية بين المنتخبين المحليين؟. 2/ كيف تؤثر هذه المعوقات على العملية التنموية؟. 3/ ما هي سبل مواجهتها(الاقتراحات)؟. Abstract: The community council is the basic unit in any political system and it is the first unit in a pyramid structure of an administrative institution, as it is the basic unit through which the local development be realized. However; usually we find lots of obstacles that hamper the realization of the local development, so; we can consider that the absence of the communication Channel between the members of the community councils is the most important obstacle. This leads me to ask the following questions: 1*what are the obstacles of the communicative process between local elected. 2*how could this obstacles could influence the development process 3*what are the ways to face this problem (suggestions).
Keywords: لكلمات المفتاحية : العملية الاتصالية؛ المنتخبين؛ التنمية؛ المحلية؛ المعوقات. ; Keywords: The communication process; elected; development; local; constraints.